marry too far
marry Men formerly admonished their sons, "You don't want to marry too far; you can't xx trust them," that is, do not marry a girl from too far away, too much of a stranger. PRINTED ITEM DNE-cit G. M. Story JAN 1970 JH 1/70 Used I Used I Used I